(untitled) (Pravaha, 2020)
The main purpose of this study is to analyze the impact of EPS, DPS, BPS, and P/E ratio on the stock price of manufacturing firms listed in NEPSE from 2072 to 2076. In this study, the data of four manufacturing firms listed in NEPSE have been studied. The descriptive and causal-comparative research designs were used to analyze the impact of EPS, DPS, BPS, and P/E ratio on MPS. The DPS and BPS negative significant impact on the stock price of the market and the EPS and P/E ratios are insignificant so they cannot predict the stock price of the market. The study also revealed that the valuable stock is UNI-Lever and the more risky firm is SHIVM cement on the study of manufacturing firms, listed in NEPSE.